2010
DOI: 10.1055/s-0030-1249924
|View full text |Cite
|
Sign up to set email alerts
|

Female Gender Does Not Increase Perioperative Risk in Coronary Bypass Surgery

Abstract: Female gender itself did not present as an independent risk factor. The presence of diabetes mellitus increased the risk in female patients significantly more than in male patients. The higher prevalence of diabetes in female patients in combination with the older age at presentation might result in the higher overall mortality observed in female patients compared to men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
3
6
0
1
Order By: Relevance
“…The example in Fig 1 shows that risk score calculation substantially overestimates true risk, an error that is corrected if the factor “female sex” is excluded from calculation. This finding is supported by several other studies that also found that female sex is not associated with increased mortality [ 6 , 14 , 26 ]. Some studies even suggested a protective effect of female sex on long term survival after CABG [ 1 , 27 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The example in Fig 1 shows that risk score calculation substantially overestimates true risk, an error that is corrected if the factor “female sex” is excluded from calculation. This finding is supported by several other studies that also found that female sex is not associated with increased mortality [ 6 , 14 , 26 ]. Some studies even suggested a protective effect of female sex on long term survival after CABG [ 1 , 27 ].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, our results and those of others [ 1 , 6 , 14 , 26 , 27 ] suggest that the impact of female sex as a risk factor in coronary artery bypass surgery should be re-evaluated and current risk scores should be readjusted specifically for this older patient population.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, our data are in line with several reports published recently [14,15]. On the other hand, several studies using STS database data from up to almost 345,000 participants identified female gender as an independent risk factor despite adjusting for risk profile [6,16].…”
Section: Discussionsupporting
confidence: 93%
“…In very high-risk patients, female and male mortality rates after CABG were found to be similar, whereas female gender was otherwise an independent predictor of higher operative CABG mortality [ 5 ]. In other studies, no gender-specific differences for perioperative mortality [ 11 ] and for long-term survival after CABG were observed [ 1 , 12 14 ]. Older age, previous CABG, previous MI and diabetes were independent risk factors for higher mortality, but female gender was not [ 15 ].…”
Section: Introductionmentioning
confidence: 92%